Path choice in transport systems: comparing random, quantum, and fuzzy utility models in a small network - Vitetta, Antonino (Frontiers in Future Transportation, 2025)
This paper considers the problem of path choice models in transport systems. It is studied within the wider problem of choice models. The main issues discussed are the classification of the utility choice model, also considering the non-random classes as quantum and fuzzy; the specification of path choice with particular reference to the easy-to-apply models within the assignment model; and a numerical results comparison in a small test system to allow the results control in each element and the reproduction. The random, quantum, and fuzzy utility models are different, and the validity of each must be tested case by case. With the assumed parameters, the models cover different trends in simulating paths overlapping. The models require application in a real system and calibration of the parameters with real data.